Contracting out temporary help services in Germany - Elke J. Jahn; Wolfgang Ochel (Center for Economic Studies and ifo Institute (CESifo), 2005)
Since 2003 the German Public Employment Service (PES) has been experimenting with the contracting out of various services. One of the new labour market programmes is the Personnel Service Agencies, which provide client firms with jobseekers on a temporary assignment basis and are responsible for integrating jobseekers into non-subsidised employment. By contracting out employment services, the PES seeks to exploit efficiency gains characteristic of enterprises that compete in quasi-markets. In order to integrate jobseekers as rapidly as possible, a result-oriented system of incentives has been developed. This paper describes the institutional setting and examines its appropriateness for efficient job placement services.
Keywords: J64; J41; J23; L33; 330; contracting out; quasi-markets; temporary agency work; Personnel Service Agency; Personalberatung; Leiharbeit; Arbeitsvermittlung; Outsourcing; Ökonomischer Anreiz; Deutschland